Systematic review with meta-analysis: encapsulated faecal microbiota transplantation – evidence for clinical efficacy - Cold, Frederik; Baunwall, Simon Mark Dahl; Dahlerup, Jens Frederik; Petersen, Andreas Munk; Hvas, Christian Lodberg; Hansen, Lars Hestbjerg (Therapeutic advances in gastroenterology, 2021)
Background: Faecal microbiota transplantation (FMT) is an effective treatment of recurrent Clostridioides difficile infection (rCDI) and is being applied experimentally in other diseases. Encapsulated administration may be equivalent in efficacy to delivery through other routes. Methods: A systematic review was undertaken of studies using encapsulated FMT up to 26 October 2020. Data on indication, clinical outcomes, safety, treatment protocol and capsule preparation were collected and reported. Pooled rates of clinical efficacy in rCDI were calculated using random-effects meta-analysis. The impact of single variables on clinical efficacy was evaluated using univariate meta-regression. Results: A total of 35 studies reporting the treatment of 960 patients with encapsulated FMT for eight different indications met the inclusion criteria. Most studies (n = 18, 51%) and patients (n = 755, 79%) were from studies on rCDI. Cure rates after single and multiple courses of treatments with encapsulated FMT in rCDI were 85% (95% CI: 82%-88%) and 93% (95% CI: 88%-96%) respectively. The treatment outcome was not significantly affected by dose, number of delivered capsules, anaerobic/aerobic processing, single/multi-donor treatment, lyophilisation, or any other single factor in the production or delivery of encapsulated FMT. Promising but non-comparable results from the treatment of ulcerative colitis and multidrug-resistant organisms were reported. Conclusions: Encapsulated FMT is an effective and safe treatment of rCDI, with cure rates comparable to FMT delivered through other routes. The treatment is effective despite variations in donor screening, preparation and treatment protocol. For other indications, the role of FMT capsules is still not sufficiently examined, although some studies show promising results. Plain Language Summary Transfer of faecal material through capsules in the treatment of various diseases. Evidence for clinical efficacy The bacteria and other microorganisms of the gut is different in patient with various diseases in comparison with healthy subjects. Therefore, ways to change the microorganisms of the gut in a beneficial direction has been the subject of various research projects within recent years. Faecal microbiota transplantation often referred as FMT is a method of transferring microorganisms from healthy donors to patients with various diseases and is seen as one way to change the microbial community of the gut in a beneficial direction. Faecal microbiota transplantation can be performed in different ways such as through endoscopy, enemas or capsules. The transfer through capsules is preferred by the patients and has advantages since it can be administered long-term and can be delivered to the patients in their home. In this paper, we evaluated all accessible research reporting treatment with encapsulated faecal microbiota transplantation in the treatment of various diseases. We report the following major findings: -Treatment with capsules is safe when guidelines for screening donors and testing faecal material is followed. -The treatment is highly effective in the treatment of recurrent C. difficile infection, a disease with high mortality often caused by repeated antibiotic treatments. The treatment was effective in 596 of 723 patients following one course of capsule treatment. -Faecal microbiota transplantation delivered through capsules is as effective as treatment delivered through other routes in the treatment of C. difficile infection. -The treatment is effective in the treatment of C. difficile infection across studies and countries, despite great differences in the ways the capsules were prepared and delivered. -Increasing the amount of faecal material used in the production did not affect the efficacy of the treatment. -There are promising results in the treatment of other diseases such as liver disease, inflammatory bowel disease and the treatment of multi-drug resistant bacteria.